Hypercapnia protects erythrocytes against free radical damage induced by hypoxia in exposed rats - Skoumalová, Alice; Herget, Jan; Wilhelm, Jirí (Cell biochemistry and function, 2008)
Several studies report that hypoxic exposure induces free radical oxidative damage in various tissues. The mechanism of this damage includes membrane lipid peroxidation which can be easily detected by measuring fluorescent end-products of the process, i.e. lipofuscin-like pigments. Four day exposure of rats to hypoxia (10% O(2)) increased the level of lipofuscin-like pigments in erythrocytes up to 9 fold. This increase was completely prevented when the animals were exposed to hypercapnia (4.3% CO(2)) in addition to hypoxia. We studied the possible mechanism of the hypercapnic protection on isolated erythrocyte membranes in vitro. Lipid peroxidation was initiated by incubation of the membranes with iron ions and ascorbate. Production of malonaldehyde, the precursor of lipofuscin-like pigments, was strongly inhibited in bicarbonate buffer. Similarly the production of lipofuscin-like products was damped. These experiments suggest that the protective effect of hypercapnia might consist in direct interaction of CO(2) with free radical processes.
Keywords: Luminescence; železo; Spectrometry, Fluorescence; Malondialdehyde; Iron; Lipofuscin; volné radikály; Erythrocytes; fluorescenční spektrometrie; Cytoprotection; peroxidace lipidů; Erythrocyte Membrane; krysa rodu Rattus; Time Factors; Hypoxia; cytoprotekce; zvířata; hyperkapnie; Free Radicals; Hypercapnia; potkani Wistar; časové faktory; hypoxie; lipofuscin; Rats, Wistar; Male; erytrocytární membrána; luminol; erytrocyty; Rats; Luminol; Animals; mužské pohlaví; malondialdehyd; luminiscence; Lipid Peroxidation